Specific composition of crabs of the family Parthenopidae- order Decapoda in the Syrian marine waters (Latakia University Journal -Biological Sciences Series, 2023)
This study provides information about the status of  Brachyuran crabs belonging to the family Parthenopidae in the Syrian marine waters, which includes about six known species in the Mediterranean. Two of them were recorded in the Syrian marine waters in previous studies: Parthenope angulifrons and Parthenope macrochelos, and their presence was re-documented through several samples collected during this study. A new species of this family was recorded for the first time in the Syrian marine waters and in the eastern basin of the Mediterranean Sea, Known as Distolambrus maltzami (Miers, 1881). This species is characterized by its small size and its spread in different regions of the Mediterranean Sea and at varying depths. During this study, we found one sample of this rare crab, Distolambrus maltzami, using a fishing nets in the marine waters of the city of Banias, at a depth ranging between 100 and 125 meters. This individual is a female with a carapace length of 11 mm and a width of 12 mm, and represents the first specimen of this species to be collected in Syrian marine waters.